2011
DOI: 10.1007/s00464-011-1628-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of postoperative intraabdominal abscesses in open versus laparoscopic appendectomies

Abstract: No significant difference in the occurrence of IAA after LA versus OA was found. The patients with complicated appendicitis experienced a greater number of IAA than the patients with uncomplicated appendicitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 13 publications
3
53
0
3
Order By: Relevance
“…The current literature demonstrates conflicting evidence with some studies suggesting that LA is associated with a higher risk of developing pelvic sepsis, 13,14,18,22 and other studies concluding that this is not significant. 8,[10][11][12]16,19,21 Our study reports 19 patients with pelvic sepsis (laparoscopic n = 2, open n = 17) demonstrating no statistically significant difference in pelvic sepsis between the two operative groups (p = 0.1184). Although there was no significant difference, LA was associated with a decreased risk of pelvic sepsis.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…The current literature demonstrates conflicting evidence with some studies suggesting that LA is associated with a higher risk of developing pelvic sepsis, 13,14,18,22 and other studies concluding that this is not significant. 8,[10][11][12]16,19,21 Our study reports 19 patients with pelvic sepsis (laparoscopic n = 2, open n = 17) demonstrating no statistically significant difference in pelvic sepsis between the two operative groups (p = 0.1184). Although there was no significant difference, LA was associated with a decreased risk of pelvic sepsis.…”
Section: Discussionmentioning
confidence: 66%
“…The majority of collections were found in the RIF, pelvis and right paracolic gutter, this does not support the mechanism of possible diffusion that has been mentioned in the literature to date. 10,13,18 Further studies have evaluated the rates of pelvic sepsis in complicated appendicitis and have concluded that there is a statistically significant increase in pelvic sepsis rates in patients with complicated appendicitis. 10,13,18,22 Frazee and Bohannon 14 published a retrospective analysis in which 19 patients with perforated appendicitis and 15 patients with gangrenous appendicitis underwent LA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations